Anaphora Relations in Lutsotso - Odera, Hellen; Barasa, David; Mudogo, Benard (Nairobi Journal of Humanities and Social Sciences, 2025)
This paper examines anaphora relations in Lutsotso, a variety of the Oluluhyia language spoken in Western Kenya. Anaphora involves words or phrases referring to entities in discourse, essential for coherence in communication. Based on data from Lutsotso conversations and texts, the study identifies and classifies anaphoric elements, focusing on reflexives and reciprocals. Reflexive constructions in Lutsotso use morphemes like -i- or -eene- to indicate that two arguments in an action refer to the same entity. The reflexive marker -i- is a prefix positioned before the verb root. Additionally, reciprocals, marked by the pronoun -an, function as anaphoric elements in the language. This study of Lutsotso anaphora enhances understanding of linguistic structures, pragmatic principles, cross-linguistic variation, and cognitive processes in language.